All Write : A Student Handbook for Writing & Learning - Kemper, Dave; Sebranek, Patrick; Meyer, Verne; Illustrated by Chris Krenzke and Mary Ross (Wilmington, Massachusetts, 1998)
Helps students build skills in writing, learning, proof-reading, grammar and test-taking.
Including color Illustration,Maps and Index
Keywords: Report writing -- Study skills -- English language--Composition and exercises